ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Novianti; Lessa Roesdiana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Learning mathematics is something that must be done by students because mathematical problem solving ability that obtained from learning process are very necessary in students daily lives. The purpose of this research was to describe mathematical problem solving ability of high school student to solve the linear equations in three variables question. The population of this research was 30 student of 10th grade student of SMA Negeri 1 Klari. The sample of this research was determined by purposive sampling and obtained 6 students with different ability. The data collection was done by giving the test of the mathematical problem solving which had 5 story questions. The result of this research is (1) The student with high problem solving ability could solved the problem given to them though they didn’t check the answers back, (2) The student with medium problem solving ability could also solved the problem given to them though they were not completely understood what was asked on question so mistakes happened at the last part also didn’t check their answers, and (3) The student with low problem solving ability didn’t write down the process as to how they got the answer and also didn’t check back the answer they got. From the results of this research, we know that students mathematical problem solving abilities are still lacking because of that it is necessary to find a way to improve students mathematical problem solving abilities.